The Effect of Work Environment, Motivation, and Compensation on Employee Job Satisfaction - Parawangsa, Duta; Ariani, Misna; Arrywibowo, Imam (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to determine the effect of work environment, motivation, and compensation on employee job satisfaction at PT. Hasta Nusa Indah Balikpapan. Job satisfaction is one of the important factors that can influence employee productivity and loyalty to the company. This research uses a quantitative approach with a survey method by distributing questionnaires to employees as respondents. The data analysis technique used is Partial Least Squares (PLS) with the help of SmartPLS software. The results show that the work environment, motivation, and compensation each have a positive and significant effect on employee job satisfaction. A safe and comfortable work environment, high work motivation, and a fair and transparent compensation system are proven to improve employee job satisfaction. Based on these findings, the company is advised to continuously improve and develop these aspects in order to maintain sustainable job satisfaction.